2020
DOI: 10.1007/s11095-020-02920-x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Skin Pharmacokinetic Data: Insights from a Topical Bioequivalence Study Using Dermal Open Flow Microperfusion

Abstract: Purpose Dermal open flow microperfusion (dOFM) has previously demonstrated its utility to assess the bioequivalence (BE) of topical drug products in a clinical study. We aimed to characterize the sources of variability in the dermal pharmacokinetic data from that study. Methods Exploratory statistical analyses were performed with multivariate data from a clinical dOFM-study in 20 healthy adults evaluating the BE, or lack thereof, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…In addition, the skin has high inter-and intraindividual variability that may depend on various physiological factors including skin color, age, sex, and anatomical location [3]. Any of these variables, individually or in combination, may influence the skin permeability or barrier properties [4]. All commercially available transdermal patches are approved for application only at specific body sites because of the variation in drug absorption that can occur from application to other locations on the body [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the skin has high inter-and intraindividual variability that may depend on various physiological factors including skin color, age, sex, and anatomical location [3]. Any of these variables, individually or in combination, may influence the skin permeability or barrier properties [4]. All commercially available transdermal patches are approved for application only at specific body sites because of the variation in drug absorption that can occur from application to other locations on the body [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the main clinical dOFM BE study, the generic test product and the reference product are tested in parallel by applying them on adjacent application sites in the same healthy participant. This design reduces inter-subject variability and thus lowers the number of participants needed for clinical PK-based dOFM studies relative to clinical endpoint studies ( Bodenlenz et al, 2020 ). A high level of standardization in each study is necessary irrespective of the tested drug products.…”
Section: Clinical Pk-based Dofm Studiesmentioning
confidence: 99%
“…In addition, dOFM studies have also shown a low intra-subject variability (9%–18% log AUC) ( Bodenlenz et al, 2020 ) indicating reproducibility due to high methodological standardization. All dOFM material and study procedures have been thoroughly optimized and highly standardized in the last few years which includes the use of template frames for probe placement, skin pre-cooling procedures, probe depths monitoring (by ultrasound), room temperature and humidity control, skin care before the study, implantation procedure, and substance application procedure, all of which led to high‐quality data that enable successful BE assessment.…”
Section: Strengths Of Dofm For Pk-based Be Studiesmentioning
confidence: 99%
“…Human and/or minipig concentrations of various drugs in the dermis or epidermis assessed by methods such as OFM, mass spectroscopy imaging, and LCM have illustrated that drug concentrations in viable skin are a fraction of that found in the SC. In humans, for example, studies with OFM have measured average dermal concentrations of an antiviral (acyclovir) and phosphodiesterase inhibitor (LEO 29102) ranging from ~10 to 1000 nM when applied topically (Bodenlenz et al, 2020;Eirefelt et al, 2020). Likewise, in a pig OFM study, dermal interstitial fluid concentrations of the Janus kinase inhibitors tofacitinib and LEO 27319A were measured at ≤ 100 nM (Handler et al, 2021).…”
Section: Drug Concentrations In Skinmentioning
confidence: 99%